Hubungan Antara Tingkat Stres Dengan Proses Adaptasi Pada Mahasiswa Baru Keperawatan S1 Universitas Muhammadiyah Purwokerto - -, Yuni; Nurjanah, Siti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: This research aimed to discover the correlation between the stress levels and the adaptation process of new students in the Undergraduate Nursing Program of Universitas Muhammadiyah PurwokertoMethods: This was a quantitative research with analytic survey design and cross-sectional method. Respond in this study as many as 155 people.The research sample using a stratified random sampling technique. The research data were collected using PSS and SACQ questionnaires. Then the data obtained were analyzed using the Chi-square test Results: There were 20 (12.9%) respondents who experienced mild stress. 110 (71%) respondents experienced moderate stress and 25 (16.1%) respondents experienced severe stress. 56 (36.1%) respondents showed moderate adaptation and 99 (63.9%) respondents showed high adaptation. The Chi-Square result from this study was p-value = 0.04Conclusion: There is a correlation between the levels of stress and the adaptation process of new students in the Undergraduate Nursing Program of Universitas Muhammadiyah Purwokerto.